2016
DOI: 10.1007/s00421-015-3325-3
|View full text |Cite
|
Sign up to set email alerts
|

Nordic hamstring exercise training alters knee joint kinematics and hamstring activation patterns in young men

Abstract: This study provides some insight into potential mechanisms by which an eccentric hamstring exercise programme utilizing the NHE as the mode of exercise may result in an improvement in hamstring muscle control during eccentric contractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 39 publications
7
84
1
2
Order By: Relevance
“…Therefore, we included 10 studies in this systematic review. [38][39][40][41][42][43][44][45][46][47] Figure 1 shows the selection process.…”
Section: Results Of Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we included 10 studies in this systematic review. [38][39][40][41][42][43][44][45][46][47] Figure 1 shows the selection process.…”
Section: Results Of Study Selectionmentioning
confidence: 99%
“…The methodologic quality assessment is provided in Figure 2 and Table 2. Five studies [38][39][40]45,47 reported the assessors were blinded. Only 4 studies demonstrated no differences in outcome measurements 42,44,45,47 or population characteristics 38,40,44,47 across study groups before the intervention.…”
Section: Methodologic Quality Assessment Of the Included Studiesmentioning
confidence: 99%
“…Specifically, infrared markers were placed on each participant's (from the bottom to the top) lateral malleolus, lateral femoral condyle, greater trochanter, and at the mid‐axillary line, just above the hip. A similar setup has been previously utilized in our research laboratory . This setup allowed for the changes in the knee joint angle (lateral malleolus and greater trochanter rotating about lateral femoral condyle) and the hip joint angle (mid‐axillary and lateral femoral condyle rotating about greater trochanter) to be recorded on the Codamotion software in real time.…”
Section: Methodsmentioning
confidence: 99%
“…A similar setup has been previously utilized in our research laboratory. 25,27 This setup allowed for the changes in the knee joint angle (lateral malleolus and greater trochanter rotating about lateral femoral condyle) and the hip joint angle (midaxillary and lateral femoral condyle rotating about greater trochanter) to be recorded on the Codamotion software in real time. The markers were attached after the MVC tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation